Fracture Resistance of Root Canals Obturated with Gutta-Percha versus Resilon with Two Different Techniques - Ashraf, Hengameh; Momeni, Golnaz; Moradi Majd, Nima; Homayouni, Hamed (Iranian Endodontic Journal, 2013)
Introduction: Dentin removal during root canal instrumentation creates a weaker root structure and increases its potential to fracture. The aim of this in vitro experimental study was to compare fracture resistance of teeth filled with gutta-percha, and Resilon using two different techniques. Materials and Methods: This study was performed on 105 single-canal extracted maxillary incisors. Samples were divided into seven groups of 15 each. Three groups were prepared with K-files; three groups with Race rotary files and in one group no preparation was carried out. Of all samples prepared either manually or with rotary instruments, 15 teeth were obturated using gutta-percha and AH26 sealer, 15 teeth were filled with Resilon and 15 teeth remained unfilled. Loading force to fracture was measured and ANOVA and Tukey tests were used for statistical analysis. Results: No statistically significant differences were observed between different preparation techniques. The intact roots showed significantly greater fracture resistance compared to both instrumented groups (P<0.01). Resilon Group showed significantly higher resistance than gutta-percha Group (P<0.01); however the difference between Resilon and intact teeth was not statistically significant. Conclusion: Accoding to the results of this in vitro study, root canal filling using Resilon may increase the fracture resistance of treated teeth.